Student’s Mathematics Anxiety on The Use of Technology in Mathematics Learning - Endang Istikomah; Astri Wahyuni (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2018)
This study aim to describe the student’s mathematics anxiety on the use of technology in mathematics learning. It is a quantitative descriptive research by involving second year students of Mathematics Education Program  in Universitas Islam Riau (UIR) who took Technology-based Mathematics Learning course. They were selected based on saturation sampling. Data were collected through questionnaire, in-depth interview and documentation. The results show the high level of each dimension of mathematics anxiety among students. The average score in each indicator of cognitive, affective, and physiological dimension were high. In addition, interview revealed that most of the students expressed their anxiety in the first lecture and when obtained the task of applying particular software in mathematics learning. It is mainly due to unpreparedness and lack of knowledge about the application of software. Based on the results, it can be concluded that the level of students’ mathematics anxiety is relatively high.  Keywords: Mathematics anxiety, Technology-based, Mathematics learning,